1982
DOI: 10.1902/jop.1982.53.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Healing Following Open Debridement Flap Procedures: I. Clinical Assessment of Soft Tissue and Osseous Repair

Abstract: The healing response of the periodontium was evaluated after periodontal flap and debridement procedures in patients with different levels of postsurgical plaque control. Thirty-one sites in 19 patients were included. Measurements were performed from a fixed reference point presurgically and before reentry surgery. All reentries were performed 24 to 28 weeks after surgery. Surgery consisted of elevating an inverse bevel mucoperiosteal flap, debriding root accretions and osseous defects, penetrating into the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 15 publications
3
36
1
Order By: Relevance
“…Kohler and Ramfjord found an average loss of 0.23 mm after MWF (Kohler & Ramfjord 1960), whereas Froum et al showed a bone loss that reached 0.8 mm (Froum et al 1982). Kohler and Ramfjord found an average loss of 0.23 mm after MWF (Kohler & Ramfjord 1960), whereas Froum et al showed a bone loss that reached 0.8 mm (Froum et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Kohler and Ramfjord found an average loss of 0.23 mm after MWF (Kohler & Ramfjord 1960), whereas Froum et al showed a bone loss that reached 0.8 mm (Froum et al 1982). Kohler and Ramfjord found an average loss of 0.23 mm after MWF (Kohler & Ramfjord 1960), whereas Froum et al showed a bone loss that reached 0.8 mm (Froum et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…19 Only small changes may occur after that up to 12 months.20 Studies evaluating probing depth and clinical attachment changes following GFS have reported improvements similar to those herein reported including probing depth reduction amounting to 3.3 mm and clinical attachment gain amounting to 2.0 mm. [21][22][23][24][25][26][27][28][29] reported probing depth reduction in areas with limited bone regeneration,29 likely an effect of postsurgery gingival recession combined with improved clinical attachment. In the present study, GFS similarly resulted in a significant probing depth reduction concurrent with limited bone level improvements.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This process includes maturation of the gingival connective tissue, formation of long epithelial attachment along the root surface previously exposed to the periodontal pocket, and minimal new connective tissue attachment and bone regeneration. [1][2][3][4] This process includes maturation of the gingival connective tissue, formation of long epithelial attachment along the root surface previously exposed to the periodontal pocket, and minimal new connective tissue attachment and bone regeneration.…”
mentioning
confidence: 99%